Business Internal Auditing – An Effective Approach in Developing Sustainable Management Systems - PUCI, Jona; GUXHOLLI, Suzana (European Journal of Sustainable Development, 2018)
Sustainability is a concept that expands on a larger perspective than the economic, environmental, and social challenges faced by a business on the daily and future operations. Sustainability refers to the ethical dimension of these operations, affecting the stakeholders of the organization and the planet on a larger scale. In this sense, more and more, the Board of Directors and other stakeholders of companies consider sustainable development as an essential part of corporate governance. In nowadays business culture, the success of a company is not only measured in terms of monetary profitability, but also in the sense of social awareness and consciousness. An increasing number of businesses are proactively adapting their internal management systems to adjust for the new requirements and transform it in a competitive advantage. These developments provide opportunities for internal auditing to contribute with its independent role within the company and objective assurance services of the internal processes, in generating sustainable value and performance of the organization. In this perspective, the aim of this study is to examine the system of sustainable internal audit that is an indispensable element for the development and well performance of sustainable management systems. Keywords: Internal Auditing, Corporate Social Responsibility, Business, Corporate Governance; Sustainable Development, Sustainable Management Systems